Regulação da expressão da óxido nítrico sintase induzível em células da granulosa bovina e o seu envolvimento com a dominância folicular - Zamberlam, Gustavo de Oliveira (2009)
Nitric oxide (NO) is an important regulator of ovarian activity, and is produced by a family of nitric oxide synthases (NOS), being inducible (iNOS) and endothelial (eNOS) isoforms present in the ovaries of several species. In cows, even though NO production had been demonstrated in follicular fluid and by granulosa cells (GC) cultured in vitro, it is not known which enzyme is responsible for NO synthesis or how expression is regulated during follicular development. The objectives of the present study were to determine the abundance of iNOS and eNOS mRNAs in dominant and subordinate follicles in vivo, to determine the regulation of iNOS expression by FSH, growth factors and estradiol (E2) in vitro, to stimulate NO production in bovine CG and to determine the action of iNOS on bovine granulosa cell health/apoptosis. The two largest follicles on days 1 to 5 of the first follicular wave of the cycle were collected from each pair of ovaries from six cows. Dominant follicles presented higher levels of mRNA for iNOS compared to subordinate follicles (P<0.01). GC cultures were performed with ovaries collected at abattoir. FSH (P<0.05) and IGF1 (P<0.01) stimulated E2 secretion and upregulated iNOS mRNA abundance in a dose-dependent manner. Moreover, both FGF2 (P<0.05) and EGF (P<0.01) decreased iNOS expression and E2 secretion in FSH and IGF-treated cells, respectively. Graded doses of FSH in the presence of a non-aromatizable androgen (DHT) did not stimulate iNOS mRNA level. In addition, both FSH and IGF1 in the presence of an estrogen receptor antagonist were not able to upregulate iNOS mRNA abundance, whereas E2 alone stimulated NO production in vitro. In terms of cell health/apoptosis, the treatment with an iNOS-selective inhibitor increased the pro-apoptotic factor FasL mRNA levels and the percentage of dead cells (P<0.05). In conclusion, bovine granulosa cells express predominantly iNOS, and increased iNOS mRNA levels are associated with emergence of the dominant follicle. FSH and IGF1 stimulate iNOS mRNA levels through increased E2 secretion, and physiological levels of NOS activity may contribute to growth and survival of bovine granulosa cells.